Inquérito Alimentar Nacional e de Atividade Física, IAN-AF 2015-2016: relatório metodológico - Lopes, Carla (2019)
Consórcio: Faculdade de Medicina da Universidade do Porto (Carla Lopes, Milton Severo, Andreia Oliveira) Instituto de Saúde Publica da Universidade do Porto (Elisabete Ramos, Sofia Vilela) Faculdade de Ciências da Nutrição e Alimentação da Universidade do Porto (Duarte Torres, Sara Rodrigues); Instituto Nacional de Saúde Doutor Ricardo Jorge (Sofia Guiomar, Luísa Oliveira); AIDFM - Faculdade de Medicina da Universidade de Lisboa (Paulo Nicola, Violeta Alarcão); Faculdade de Desporto da Universidade do Porto (Jorge Mota); Faculdade de Motricidade Humana da Universidade de Lisboa (Pedro J. Teixeira); SilicoLife (Simão Soares); Faculdade de Medicina da Universidade de Oslo, Noruega (Lene Andersen)